Identification of the Risks of Giving the Covid 19 Vaccine on Other Health Workers at Dr Mohammad Hoesin Hospital Palembang - Witri Gusti; Eva Yunila; Elsa Savitrie; Sri Laniah (RSUP Dr Moh Hoesin Palembang, 2021)
Corona Virus Disease 2019 (COVID-19) is a disease caused by the SARS-CoV-2 virus, this disease spreads faster and in a short time becomes a worldwide pandemic. In the context of controlling and preventing the spread of the COVID-19 virus, the COVID-19 vaccination is carried out. The main priority in administering the COVID 19 vaccination is health workers because they are at high risk of being exposed to the COVID 19 virus. Other Health Workers who are included in the Committee for other Health Workers at Dr Mohammad Hoesin Hospital Palembang also receive the COVID-19 vaccination which is carried out in 2 doses or 2 injections. The COVID-19 vaccination may pose a risk of local or systemic side effects. This study aims to identify the risks that arise after administering the COVID-19 vaccine to other health workers at Dr Mohammad Hoesin Hospital Palembang. The design of this study was quantitative using an analytical survey method through a retrospective approach. The population is 534 people consisting of 20 other health professions. Based on the data analysis, it can be concluded that the risks that arise after the administration of the COVID -19 I Vaccination are in the form of systemic side effects, namely drowsiness (67%) and local side effects are pain (58.5%), while after the second Covid 19 vaccination, the most common side effects are pain. Common side effects are local side effects, namely pain (77.3%) and systemic side effects are drowsiness (62.1%). occurred after the administration of the first Covid 19 vaccination (86.2%). After giving the COVID 19 vaccination, there were still 5 other Health Workers who were exposed to the Covid 19 virus (4.6%).